KARAKTERISASI VIRGIN COCONUT OIL (VCO) REMPAH - Gugule, Sanusi (Sam Ratulangi University, 2010)
ABSTRACTGugule, S. and F. Fatimah. 2010. Characterization of spices virgin coconut oilA study has been carried out to find out the effect of some spices type on quality and characteristic of fatty acid of virgin coconut oil (VCO). The test of spice VCO quality conducted with the determination of iodine and acid number, water content and peroxide number. The profile of fatty acid of VCO was tested with the liquid gas chromatography, using the internal standard of margaric acid. The experimental result showed that control and spice VCO that is VCO nutmeg, leaf of salam, sweet basil and galingale have the quality fulfilling standard APCC, except number iodine. As compared to control, the addition of spice at making VCO nor have an effect to fatty acid percentage in VCO, but having an effect to reduction fatty acid content in VCO (calculated in mg / 100g sample)..Kata kunci : Characterization, virgin coconut oil, spices